Increased UV radiation due to polar ozone chemical depletion and vortex occurrences at Southern Sub-polar Latitudes in the period [1997–2005] - E. J. Quel; A. Hauchecorne; R. D. Piacentini; E. A. Luccini; S. Godin-Beekmann; A. F. Pazmiño (Copernicus Publications, 2008)
The variability of total ozone and UV radiation from Total Ozone Mapping Spectrometer (TOMS) measurements is analyzed as a function of polar vortex occurrences over the southern subpolar regions during the 1997–2005 period. The analysis of vortex occurrences showed high interannual variability in the 40° S–60° S latitude band with a longitudinal asymmetry showing the largest frequencies over the 90° W–90° E region. The impact of vortex occurrences on UV radiation and ozone in clear sky conditions was determined from the comparison between the measurements inside the vortex and a climatology obtained from data outside the vortex over the studied period. Clear sky conditions were determined from TOMS reflectivity data. For measurements outside the vortex, clear sky conditions were selected for reflectivity values lower than 7.5%, while for measurements inside the vortex, a relaxed threshold was determined from statistically similar UV values as a function of reflectivity. UV changes and ozone differences from the climatology were analyzed in the 40° S–50° S and 50° S–60° S latitude bands during the spring period (September to November). The largest UV increases and ozone decreases, reaching ~200% and ~65%, respectively, were found in the 50° S–60° S latitude band in September and October. The heterogeneous ozone loss during vortex occurrences was estimated using a chemical transport model. The largest impact of vortex occurrences was found in October with mean UV increase, total ozone decrease and accumulated ozone loss in the 350–650 K range of, respectively, 47%, 30% and 57%. The region close to South America is the most affected by the Antarctic ozone depletion due to the combined effect of large number of vortex occurrences, lower cloud cover and large ozone decrease. This region would be the most vulnerable in case of cloud cover decrease, due to more frequent occurrence of ozone poor air masses during austral spring.